ANALISIS SPIRIT ENTREPRENUR BISNIS COFFEE TO GO DALAM MEMBIDIK KAUM MILLENIAL DI INDONESIA - Agus Garnida (Jurnal Sekretaris dan Administrasi Bisnis, 2021)
Every entrepreneur plays a role as an agent of change in developing a business, the ability of entrepreneur to look for business opportunities that create value that can increase orgnaizational sustainability. Entrepreneurial spirit can emerge because of the encouragement of trends that occur in the target market. The target market for coffee entrepreneurs is also triggered by changes in customer behaviors trends, especially millennials, which are identical to the internet. The purpose of this research is to analysis how spirit the entrepreneur coffee to go in attaching millenials in Indonesia. The research method used is descriptive discussion. Data collection techniques were carried out by observation, and literature studies from books, journals, and documents related to research discussions. The results of the study show that millenials are the main target for coffee entrepreneurs and proactive attitude,innovations, and collaborations of the entrepreneur is the major successul indicator for their success in digital and pandemic era.